Water Quality Analysis of the Sengkaring River for Fish Farming Feasibility in Pekalongan Regency - Afidah, Fini; Jailani, Abdul Qadir; Aji, Muhammad Tri (Aquatic Life Sciences, 2025)
Rivers serve as essential water sources for freshwater aquaculture, and their quality must meet physical, chemical, and biological standards to ensure environmental sustainability. This study aimed to assess the water quality of the Sengkarang River in Pekalongan Regency, Central Java, Indonesia, determine its suitability for freshwater aquaculture, and identify fish species appropriate for cultivation. The research was conducted from October to November 2021 during the transitional period from dry to rainy season at three sampling sites representing the upstream (Legokalong Village), midstream (Karanganyar Village), and downstream (Karangsari Village) zones. Water samples were collected using purposive sampling and analyzed by the Environmental Agency of Pekalongan City through laboratory testing, descriptive statistics, and a scoring-based suitability assessment. The results showed that temperature (25.3–26.1 °C), brightness (38–54 cm), dissolved oxygen (5.2–5.7 mg/L), pH (7.0–7.3), BOD (0.19–1.05 mg/L), COD (20.65–35.92 mg/L), and nitrite (0.026–0.041 mg/L) met the Class III water quality standards based on Government Regulation No. 22 of 2021. Plankton abundance ranged from 47,410 to 75,000 ind/L, indicating fertile and productive waters. With an overall suitability score of 86 (highly suitable category), the Sengkarang River is considered feasible for the cultivation of Nile tilapia (Oreochromis niloticus), catfish (Clarias sp.), and gourami (Osphronemus goramy). These findings highlight the strong potential of the Sengkarang River for sustainable aquaculture development and emphasize the importance of regular environmental monitoring to maintain water quality and ecological balance.